Пікосекундна динаміка молекулярних об’єктів у розчинах солей літію в диметилсульфоксиді, пропіленкарбонаті та диметилкарбонаті - Gorobets, M. I.; Kirillov, S. A. (Publishing house "Academperiodika", 2018)
An analysis of the Raman spectra of the solutions of lithium salts in dimethyl sulfoxide, propylene carbonate, and dimethyl carbonate in a concentration range from diluted solutions to the mixtures of molten solvates with salts has been performed in terms of the dynamics, specifically, the dephasing (тv) and modulation (тw) times of all molecular entities present in solutions are determined and analyzed. It has been found that, in the picosecond time domain, the dephasing and modulation in solvent molecules hydrogen-bonded with an anion and/or solvating a cation are slower than in free solvent molecules. In solvent separated ion pairs, both тv and тw are much longer than in solvated anions, thus indicating the strong interactions between anions and their surrounding. In contact ion pairs, тv are great, whereas тw appear close to those for free anions. This reflects that the structure of the liquid tends to the structure of molten salts.